Effectiveness of Acrostic Techniques to Improve Students' Creative Poetry Writing Skills - Asmarani Dian Pertiwi; Yohan Dwi Saputra; Deny Hadi Siswanto; Putri Fuadiyanti (Academicus: Journal of Teaching and Learning, 2025)
Poetry writing competency in the Merdeka Curriculum is crucial in Indonesian language learning, but many students struggle to express creative ideas due to a lack of innovative teaching strategies. The acrostic technique, chosen for its clear structure and ability to stimulate imagination through keywords, was employed to address this challenge. This study analyzes the effectiveness of the acrostic technique in improving poetry writing skills among class VIII students at State Junior High School 3 Banguntapan. A quasi-experimental method with a Control Group Pre-test and Post-test Design was used, with two classes: the experimental class (40 students) using the acrostic technique and the control class (40 students) using conventional methods. Data were collected through tests and interviews. The findings reveal that the acrostic technique significantly improved students' writing skills compared to conventional methods, with a significance value of 0.000. This study contributes to the development of innovative teaching methods that enhance students' writing abilities in language and literature education.